Clinical and Biochemical Insights into Biofilm-Forming Bacteria Isolated from Dialysis Patients. - Kadhem, Noor; Atya, Ahmed (University of Thi-Qar Journal of Science, 2025)
Bacterial biofilms are difficult to eradicate and cause a significant number of complications in the management of dialysis patients resulting in more frequent infections and worse morbidity. The purpose of the present research paper is to study the characteristics of biofilm producing bacteria sampled from dialysis patients and their relationships with clinical and biochemical features. Urine cultures from 121 participants were used and yielded a total of 23 bacterial isolates. From the 23 samples, E. coli (n=15) had the highest frequency of moderate biofilm formation with 46.67% of the isolates belonged to this category while the rest of the isolates were equally distributed between the weak and strong biofilm producers (26.67% each). Enterobacter cloacae complex (n=3) formed moderate biofilms at a higher frequency (66.67%). On the other hand, Klebsiella pneumoniae (n=5) showed relatively weak biofilm formation, 60% had weak biofilm formation while 40% had moderate biofilm formation. We then analysed the antimicrobial resistance profiles of the isolates to determine the relationship between biofilm formation and resistance pattern. All the weak biofilm producers were multidrug-resistant while the resistance pattern of the moderate biofilm producers was also rather homogeneous; 72.7% of the isolates were multidrug-resistant and 27.3% were extensively drug-resistant.  However, the resistance pattern of the strong biofilm producers was rather different